Perancangan Paket Wisata di Desa Hambalang Kabupaten Bogor Berbasis Wisata Sport Tourism, Alam, dan Religi - Mbulu, Yustisia Pasfatima; Rossi, Fetty Nurmala; Salsabila, Aqilla Devia; Bhilhaq, Mutiara Sani (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2024)
This research aims to design a tourism package based on sport tourism, nature, and religion in Hambalang Village, Bogor Regency. The research method was descriptive qualitative, collecting field survey data or direct observation in Hambalang Village, Bogor Regency. As well as conducting interviews with the Head of Hambalang Village, the Head of the tourist village, Karang Taruna, the Chair of the MUI of Hambalang Village, MSME actors, the people of Hambalang Village, and the manager of the Environmentally Friendly Village. The results obtained from designing tour packages in Hambalang Village, Bogor Regency, are in the form of sport tourism, nature, and religious tourism-based tour packages called